Domestic dog attacks on livestock referred to a Veterinary Teaching Hospital - Gonzaga, Mariana da Costa (2024)
Losses and the economic impact of dog attacks (DAs) on livestock are often overlooked and include factors such as decreased production, expenses for treatment and handling, and death of injured animals. This study evaluated the epidemiological, therapeutic, and pathological findings of DAs on livestock over an 11-year survey using the records of farm animals referred to a Veterinary Teaching Hospital. Livestock attacked by dogs included 31 sheep, 11 horses, 3 cattle, 3 goats, and 2 pigs, totaling 50 animals. Anatomical locations injured by dog bites were identified as head/neck, thoracic/pelvic limbs, abdomen/flank, rump/tail, and multiple affected regions (two or more bite sites). Additionally, the severity of the injuries was classified into four degrees adapted from the classification of dog bite injuries in children. Most livestock presented Grade 1 (26%) and Grade 2 (28%) injuries, while Grade 3 and Grade 4 injuries were observed in 46% of DAs. Furthermore, 35 animals (70%) were discharged, 9 (18%) died, and 6 (12%) were humanely euthanized. DAs may represent a significant cause for referring livestock species to clinical care, severe injuries, and a considerable number of deaths. In this study, we provide information regarding DAs on livestock for the first time in Midwestern Brazil.